Study on the Extension of Plant Protection Measures in Agricultural Production - Planning Commission (Planning Commission, 1962)
During the last fiften years or so, chemical measures to control pasts, diseases and weeds have progressively gained in popularity although they are far from the required scale of adoption. The plant protection measures can be broadly classified. into four groups; i) Chemical control; ii) Mechanical and physical control; iii) Cultural control; iv) Biological control;
Programme Evaluation Organisation. Planning Commission Government of India
Programme Evaluation Organisation. Planning Commission Government of India